Моделі прийняття управлінських рішень в умовах воєнного стану: адаптація бізнес-стратегій до високої невизначеності - Каут, Ольга Вікторівна; Вишневська, Марія Костянтинівна (Наукова установа «Науково-дослідний центр сталого розвитку», Київ, 2026)
UKR: У статті досліджено трансформацію підходів до стратегічного управління промисловими підприємствами в умовах повномасштабної війни та зростаючої невизначеності зовнішнього середовища. На прикладі індустріального кластера Дніпропетровської області обґрунтовано необхідність переходу від детермінованих моделей стратегічного планування до стохастичних адаптивних систем управління підприємствами. Теоретичною основою дослідження стали положення стохастичної оптимізації, концепції реальних опціонів та підходи до управління стійкістю підприємств. У дослідженні застосовано методи економіко-математичного моделювання, сценарного аналізу та експертного оцінювання ризиків. Розроблено авторську математичну модель оптимізації управлінських рішень (SOCRC), що враховує воєнні ризики, енергетичну нестабільність і логістичні обмеження та дозволяє формалізувати вибір стратегій функціонування підприємств у середовищі високої невизначеності. Удосконалено науково-методичний підхід до оцінки вартості бізнес-стратегій на основі підходу реальних опціонів, у якому параметр волатильності модифіковано з урахуванням інтенсивності бойових дій, що дає змогу кількісно обґрунтовувати рішення щодо переключення виробничих потужностей або їх тимчасової консервації. Подальшого розвитку набуло поняття адаптаційного потенціалу підприємства, для якого визначено критичний коефіцієнт інвестицій в адаптацію, перевищення якого сприяє статистично значущому зниженню ймовірності банкрутства. Практичне значення результатів полягає у можливості використання розробленого інструментарію керівниками промислових підприємств для обґрунтування стратегій збереження виробничого потенціалу та забезпечення операційної безперервності в умовах воєнних ризиків.

ENG: The article examines the transformation of strategic management approaches for industrial enterprises under the conditions of full-scale war and increasing environmental uncertainty. Using the industrial cluster of the Dnipropetrovsk region as a case study, the research substantiates the necessity of shifting from deterministic models of strategic planning to stochastic adaptive management systems capable of accounting for wartime risks, logistical disruptions, and energy instability. The theoretical foundation is based on stochastic optimization theory, the concept of real options, and resilience management approaches. To formalize managerial decision-making, methods of economic and mathematical modeling were applied, including a modification of the Black–Scholes formula for assessing strategic flexibility. Empirical verification of the proposed model was carried out through scenario analysis and expert evaluation of risk parameters for enterprises within the industrial cluster of the Dnipropetrovsk region. A mathematical model for optimizing managerial decisions (SOCRC) has been developed, which incorporates wartime risks, energy instability, and logistical constraints and enables the formalization of enterprise strategy selection under high uncertainty. The mechanism for evaluating the value of business strategies has been improved through the application of the real options approach, where the volatility parameter is modified by taking into account the intensity of military actions. This allows for the quantitative justification of managerial decisions related to switching production capacities or their temporary suspension. Further development has been given to the concept of the enterprise’s adaptive potential, for which a critical coefficient of investment in adaptation has been determined. Based on the case of enterprises in the Dnipropetrovsk region, the threshold value of this coefficient is established at 12% of asset value, the exceeding of which contributes to a statistically significant reduction in bankruptcy probability. The practical significance of the results lies in the possibility of using the proposed analytical toolkit by managers of industrial enterprises to substantiate strategies aimed at preserving production potential and ensuring operational continuity under wartime risks.
Models of Managerial Decision-Making under Martial Law: Adaptation of Business Strategies to High Uncertainty
О. Каут: ORCID 0000-0003-4126-4961; М. Вишневська: ORCID 0000-0002-3580-0564
Keywords: управлінські рішення; воєнний стан; невизначеність; промислове підприємство; Дніпропетровська область; математичне моделювання; бізнес-стратегія; ризик-менеджмент; managerial decisions; martial law; uncertainty; industrial enterprise; Dnipropetrovsk region; mathematical modeling; business strategy; risk management; КМЕУіСГД; SOCIAL SCIENCES; SOCIAL SCIENCES::Business and economics